Completed durable response of advanced endometrial cancer treated with pembrolizumab without surgical intervention or systemic chemotherapy: A case report - Anusha Adkoli; Rodrigo Alcorta Proaño; Eugenia Girda (Current Problems in Cancer: Case Reports, 2024)
Endometrial cancer remains the most common gynecologic malignancy in the United States. Novel molecular targets are being explored for treatment of advanced uterine. Molecular targets in signaling cascades have been identified including immune checkpoint inhibitors. This is a case of 63-year-old G0 with locally advanced unstaged undifferentiated/dedifferentiated TMB-H/MSI endometrial cancer, who had progression of disease after neoadjuvant radiation therapy. She was intolerant of systemic chemotherapy and declined surgical intervention but had subsequent complete response after 9 cycles of pembrolizumab. She has remained disease free for a total of 30 months (about 2.5 years) of follow up. Standard of care for advanced uterine cancer includes multimodality treatment with surgery, radiation, and systemic chemotherapy. This patient's response to treatment demonstrates that immunotherapy as an upfront treatment may be a reasonable alternative for patients with endometrial cancer with specific molecular profile regardless of histology.